AI IN THE HALAL INDUSTRY: A BIBLIOMETRIC ANALYSIS OF RESEARCH TRENDS AND ESG COMPLIANCE - Candra, Wirdatul Khomro Septian; Andriani, Sri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
ABSTRACT This study conducts a bibliometric analysis to map the development of Artificial Intelligence (AI) research in the halal industry, with particular attention to emerging trends and thematic evolution. Using the Scopus database, a total of 736 publications were retrieved and analyzed through VOSviewer to identify publication trends, prolific authors, influential works, leading journals, contributing institutions, and keyword networks. The findings reveal a significant growth in publications over the past three years, particularly in 2024 and 2025, reflecting the increasing interest of academics, practitioners, and policymakers in integrating AI into the halal industry. The Journal of Cleaner Production emerged as the leading publication outlet, while China and India dominated in terms of research output, followed by the United States, the United Kingdom, and Malaysia. The most prominent keywords include artificial intelligence , sustainability , big data , machine learning , and ESG , with emerging topics such as green economy , green innovation , blockchain , and supply chain management . These findings suggest that AI adoption in the halal industry is increasingly linked to sustainability, governance, and transparency objectives. However, topics such as halal cosmetics , religiosity , and regional variations remain underexplored, presenting opportunities for future research. The study contributes to the literature by providing a comprehensive overview of the research landscape, offering insights for scholars, industry practitioners, and policymakers to advance innovation and sustainable development in the halal sector.